Eccentricity dependent auditory enhancement of visual stimulus detection but not discrimination - Gleiss, Stephanie; Kayser, Christoph (Frontiers in Integrative Neuroscience, 2013)
Sensory perception is enhanced by the complementary information provided by our different sensory modalities and even apparently task irrelevant stimuli in one modality can facilitate performance in another. While perception in general comprises both, the detection of sensory objects as well as their discrimination and recognition, most studies on audio-visual interactions have focused on either of these aspects. However, previous evidence, neuroanatomical projections between early sensory cortices and computational mechanisms suggest that sounds might differentially affect visual detection and discrimination and differentially at central and peripheral retinal locations. We performed an experiment to directly test this by probing the enhancement of visual detection and discrimination by auxiliary sounds at different visual eccentricities and within the same subjects. Specifically, we quantified the enhancement provided by sounds that reduce the overall uncertainty about the visual stimulus beyond basic multisensory co-stimulation. This revealed a general trend for stronger enhancement at peripheral locations in both tasks, but a statistically significant effect only for detection and only at peripheral locations. Overall this suggests that there are topographic differences in the auditory facilitation of basic visual processes and that these may differentially affect basic aspects of visual recognition.